2008
DOI: 10.1038/labinvest.2008.17
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein 1G acts as an oncosupressor in papillary thyroid carcinoma

Abstract: The molecular pathogenesis of tumors arising from the thyroid follicular epithelial cells, including papillary (PTC) and follicular thyroid carcinoma (FTC), is only partially understood, and the role of tumor suppressor genes has not yet been assessed. The metallothionein (MT) gene family encodes a class of metal-binding proteins involved in several cellular processes, and their expression is often deregulated in human tumors. Recently, downregulation of MT gene expression in PTC has been reported, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 30 publications
7
73
1
1
Order By: Relevance
“…Although a role for tumor-suppressor genes in thyroid carcinogenesis has not been assessed yet, functional studies have allowed some genes downregulated in PTCs to be classified as tumor suppressors, based on their ability to modulate transformed properties of thyroid tumor cell lines (Ferrario et al, 2008;Latini et al, 2008;Pallante et al, 2008;Vizioli et al, 2010;Zuo et al, 2010). With this study, we have demonstrated that TIMP3 exerts a negative regulatory role in thyroid tumor cells, thus corroborating its oncosuppressor role suggested by hypermetylation and gene expression studies.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Although a role for tumor-suppressor genes in thyroid carcinogenesis has not been assessed yet, functional studies have allowed some genes downregulated in PTCs to be classified as tumor suppressors, based on their ability to modulate transformed properties of thyroid tumor cell lines (Ferrario et al, 2008;Latini et al, 2008;Pallante et al, 2008;Vizioli et al, 2010;Zuo et al, 2010). With this study, we have demonstrated that TIMP3 exerts a negative regulatory role in thyroid tumor cells, thus corroborating its oncosuppressor role suggested by hypermetylation and gene expression studies.…”
Section: Discussionsupporting
confidence: 75%
“…To this end, we analyzed several microarray data of tumor and normal thyroid tissues. In cDNA microarray data produced in our laboratory (Ferrario et al, 2008), in comparison with TIMP3 gene expression level of normal thyroid, TIMP3 downregulation was evident in both the classical histotype and the tall cell variant (Po0.01; Figure 1a). Frequent downregulation of TIMP3 in comparison with normal samples was also observed when a number of independent data sets of microarray gene expression data of PTC samples, publicly available and all obtained using Affymetrix HG-U133 series platforms, were considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MT1G cDNA was cloned into the pcDNA3.1/mycHis(-)A expression vector, resulting in a MT1G-myc fusion protein as previously described (21). OXA and 5-FU were obtained in the pharmacy of the Alexander Fleming Institute (Buenos Aires, Argentina).…”
Section: Reagents and Cell Linesmentioning
confidence: 99%
“…Additionally, MTs can function as efficient scavengers of reactive oxygen species to preserve homeostasis of cells. The latest study have indicated a possible role of MTs as a tumor suppressor in papillary thyroid cancer [8] and their part in the distribution of metals, thereby optimizing the function of thyroid gland [4].…”
Section: Introductionmentioning
confidence: 99%